2022
DOI: 10.3390/jfb13030107
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic Potential of Co-Cultured Human Umbilical Vein Endothelial Cells and Adipose Stromal Cells in Customizable 3D Engineered Collagen Sheets

Abstract: The wound healing process is much more complex than just the four phases of hemostasis, inflammation, proliferation, and maturation. Three-dimensional (3D) scaffolds made of biopolymers or ECM molecules using bioprinting can be used to promote the wound healing process, especially for complex 3D tissue lesions like chronic wounds. Here, a 3D-printed mold has been designed to produce customizable collagen type-I sheets containing human umbilical vein endothelial cells (HUVECs) and adipose stromal cells (ASCs) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Studies have shown that MSC‐conditioned medium can improve wound healing by releasing growth factors, immunoregulatory factors, chemokines, and extracellular vesicles 17–21 . Co‐culturing MSCs with endothelial cells and keratinocytes has shown improved angiogenesis and recovered epidermal barrier function 22–25 . The efficiency of MSC delivery to damaged tissue is limited by poor cell retention and viability after application 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that MSC‐conditioned medium can improve wound healing by releasing growth factors, immunoregulatory factors, chemokines, and extracellular vesicles 17–21 . Co‐culturing MSCs with endothelial cells and keratinocytes has shown improved angiogenesis and recovered epidermal barrier function 22–25 . The efficiency of MSC delivery to damaged tissue is limited by poor cell retention and viability after application 26 .…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Co-culturing MSCs with endothelial cells and keratinocytes has shown improved angiogenesis and recovered epidermal barrier function. [22][23][24][25] The efficiency of MSC delivery to damaged tissue is limited by poor cell retention and viability after application. 26 Furthermore, cell-laden dressings require special facilities and culture conditions that can limit access and increase cost.…”
mentioning
confidence: 99%